2021
DOI: 10.1139/cjps-2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation between the reproductive traits ofAllium wallichiiKunth in central and peripheral populations

Abstract: The differentiation of reproductive characteristics not only exists between different populations, but also may exist within populations. In this work, the differences between the central and peripheral populations were experimentally compared and analyzed in terms of biodiversity index, plant traits, anthesis, pollen germination, floral visitors, seed setting rate, and ploidy. The results showed that the diversity and richness of other plant species, in the central population were significantly lower than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…During earlier classification Allium genus was placed in Liliaceae, which was later included in Amaryllidaceae on the basis of inflorescence structure (Melchior 1964). The plant is differentiated from one geographic location to another by reproductive trait (Tang 2021). In a very recent study by our group, stomata type, number and index were studied.…”
Section: Taxonomic Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…During earlier classification Allium genus was placed in Liliaceae, which was later included in Amaryllidaceae on the basis of inflorescence structure (Melchior 1964). The plant is differentiated from one geographic location to another by reproductive trait (Tang 2021). In a very recent study by our group, stomata type, number and index were studied.…”
Section: Taxonomic Classificationmentioning
confidence: 99%
“…In brief, A. wallichii is a perennial herb of higher altitude (between 2700 to 3600 m elevations) having single, conical, and short bulb (flowering during August and September and having garlic like odor), majorly habitat in Bhutan, India, Myanmar, Nepal and Southwestern China, respectively (Chhetri & Gupta 2007, Rana & Samant 2010, Huang et al 2014Chen et al 2021). The detailed pharmacognostical and phylogenetic studies revealing various identification characters has been carried out in the recent past (Tiwari et al 2014, Huang et al 2014, Paul et al 2019, Tang et al 2021. A study conducted on 110 informants suggested strong aroma for A. wallichii by 100%.…”
Section: Introductionmentioning
confidence: 99%